Overexpression of dihydroflavonol 4-reductase (CoDFR) boosts flavonoid production involved in the anthracnose resistance - Yang, Chaochen; Wu, Pengfei; Cao, Yongqing; Yang, Bingbing; Liu, Linxiu; Chen, Juanjuan; Zhuo, Renying; Yao, Xiaohua (Frontiers in Plant Science, 2022)
The outbreak of anthracnose (caused by Colletotrichum spp.) represents a devastating epidemic that severely affects oil tea (Camellia oleifera) production in China. However, the unknown resistance mechanism to anthracnose in C. oleifera has impeded the progress of breeding disease-resistant varieties. In this study, we investigated the physiological responses of resistant and susceptible lines during C. gloeosporioides infection. Our results showed that the accumulation of malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD) in both disease-resistant and susceptible lines increased by C. gloeosporioides infection. Also, disease-resistant lines exhibited lower MDA, but higher POD, SOD, and CAT activities compared to susceptible lines. The accumulation of flavonoids in both resistant and susceptible C. oleifera leaves increased following C. gloeosporioides infection, and the increase was greater in resistant lines. Further, we identified and functionally characterized the dihydroflavonol 4-reductase (CoDFR) from the resistant C. oleifera line. We showed that the full-length CDS sequence of CoDFR is 1044 bp encoding 347 amino acids. The overexpression of CoDFR in tobacco altered the expression of flavonoid biosynthetic genes, resulting in an increased flavonoid content in leaves. CoDFR transgenic tobacco plants exhibited increased anthracnose resistance. Furthermore, the transgenic plants had higher salicylic acid content. These findings offer potential insights into the pivotal role of CoDFR involved in flavonoid-mediated defense mechanisms during anthracnose invasion in resistant C. oleifera.